Facile biosurfactant assisted biocompatible α-Fe2O3 nanorods and nanospheres synthesis, magneto physicochemical characteristics and their enhanced biomolecules sensing ability. Issue 81 (15th August 2016) - Sundar, Sasikala; Mariappan, Ramalakshmi; Min, Kim; Piraman, Shakkthivel
Abstract : Tunable magnetic and electrocatalytic characteristics of α-Fe2 O3 nanostructures were fabricated by tapping saponin induced anisotropic growth, demonstrated excellent electrocatalytic activity towards dopamine and uric acid with wider potential gap. Abstract : Recently, non-spherical magnetic iron oxide nanoparticles have attracted much attention, because of their shape-dependant potential applications in biosensors and magnetic storage devices. In this work, a simple, novel, environmentally friendly, energy inexpensive, toxic free synthetic approach was utilized to synthesize α-Fe2 O3 nanorods with an aspect ratio of 10 and homogeneously dispersed 30 nm α-Fe2 O3 nanospheres (from TEM and FE-SEM images) using non-toxic "Centellasaponin" biosurfactant/capping agent tapping the big polar and non-polar head saponin induced anisotropic growth. The α-Fe2 O3 nanorods and nanospheres synthesized by the template-free, low cost, simple, energy intensive route were confirmed by FTIR, XRD and the X-ray photoelectron spectroscopy by the appearance of electron binding energy at 710.74 eV and 724.2 eV corresponding to 2P3/2 and 2P1/2 core levels of α-Fe2 O3 nanoparticles. Nano α-Fe2 O3 spheres and rods synthesized at different temperatures and various concentrations exhibit superparamagnetic characteristics consisting of a single magnetic domain of nanoparticles with no discernible coercivity and remanance with not ending magnetic saturation hysteresis and will find potential applications in magnetic recording and targeted drug delivery. Nano α-Fe2 O3 magnetic particles displayed excellent electrochemical sensing activities towards dopamine and uric acid with 320 mV and 260 mV wider separation on α-Fe2 O3 nanorods and α-Fe2 O3 nanospheres, respectively at 90–170 mV reduced potential with 100% increased current response. With good selectivity and sensitivity, the α-Fe2 O3 nanostructures could be applied in the determination of dopamine in injectable medicine and uric acid in urine samples.